RESEARCH OF FREE OSCILLATIONS OF THE BODY OF THE VEHICLE WHILE DRIVING - Kolodnenko, V.M.; Solarov, O.O. (Bulletin of Sumy National Agrarian University. The series: Mechanization and Automation of Production Processes, 2022)
Vehicle body sway refers to the movements and vibrations to which the vehicle structure itself is subjected while driving. These can be movements and vibrations that occur relative to the main structure or frame of the vehicle. During the movement of the vehicle, especially on roads with uneven surfaces, the body is subject to various vibrations. These fluctuations can be caused by unevenness on the road, the resistance of working bodies, the influence of wind forces or other factors. Types of hull oscillations may include vertical oscillations manifested as bouncing or up-and-down movements; longitudinal rocking occurring in the direction of movement of the vehicle; horizontal-longitudinal vibrations of the body, which appear due to the influence of lateral forces or movements of the body up and down; and transverse sway, known as roll, side-to-side sway. Body vibrations can affect various aspects such as passenger comfort, vehicle stability, efficiency of working organs and overall safety. Therefore, studying and understanding these fluctuations is an important task for vehicle designers and engineers working to improve their performance and functionality. In this article, we have carried out a detailed analysis of the process of oscillation of the vehicle body during movement. The study covers the effect of road surface irregularities and other factors on body vibration. It was found that various types of oscillations occur during the movement of the vehicle, such as vertical oscillations (jumping), longitudinal swaying, horizontal-longitudinal oscillations of the body and transverse oscillations (side swaying). The conducted analysis examines the causes of these fluctuations and their impact on the comfort of the driver, passengers and the stability of the vehicle. For a better understanding of the oscillation process, a mathematical analysis was carried out for the purpose of further modeling and conducting experimental studies. The results of this research can be important for improving the design of vehicles and developing effective vibration absorption systems that ensure a comfortable ride and the safety of passengers. The given calculation algorithm describes in detail the process of oscillation of the vehicle body during movement.